Mathematical Reasoning Analysis Based on Students’ Emotional Stability - Wulan Resti Oktaviani; Darhim Darhim; Nurjanah Nurjanah; Kusnandi Kusnandi (Universitas Sebelas Maret, 2024)
High school students enter adolescence, a period full of challenges, including changes in their physical, emotional, cognitive, social, and behavioral aspects. The inability to adapt to these changes often leads to problems. Therefore, problem-solving skills are necessary. This study explores the relationship between students' emotional stability and their mathematical reasoning abilities. The research aims to understand how variations in emotional stability impact the cognitive process involved in mathematical reasoning. A descriptive qualitative approach was used to examine the mathematical reasoning abilities of twelfth-grade students in Bandung. Participants were selected using purposive sampling based on specific criteria related to their emotional stability and reasoning abilities. The instruments included a mathematical reasoning test and an emotional stability questionnaire measured on a Likert scale. The results indicate that students with high emotional stability demonstrate very good mathematical reasoning abilities, meeting all relevant indicators. In contrast, students with medium emotional stability show good reasoning skills, meeting three to four indicators. Students with low emotional stability, however, fall into the poor category, meeting only one or two indicators. These findings suggest that emotional stability significantly influences students' ability to reason mathematically. The study recommends that educators create engaging and supportive learning environments to enhance students' emotional stability and, consequently, their mathematical reasoning abilities. Training programs for students with low emotional stability are advised to help them focus better and improve their cognitive abilities. Future research should further investigate the interplay between emotional stability and mathematical reasoning across different subjects and educational levels to develop more effective educational strategies.